Singapore breakers' run-up to the next stage - Chia, Kun Liang (Nanyang Technological University, 2022)
Breaking, hip-hop culture's oldest known dance, is set to make its Olympic debut at the 2024 Paris Summer Games. Despite Singapore’s bronze medal achievement at the 2019 SEA Games Breaking Men’s Single, the country’s competitive breaking scene is still a far cry from powerhouses in Asia like Japan and Korea.